2018
DOI: 10.1016/j.jvs.2017.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of recurrent endovascular intervention for cephalic arch stenosis after percutaneous transluminal angioplasty

Abstract: Multivariate analysis showed that diabetes and residual stenosis (albeit <30%) were predictive of recurrence, whereas the finding of an isolated CAS lesion as opposed to stenoses in multiple locations was shown to be negatively associated with recurrent CAS, appearing to be "protective".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…19,20 On the other hand, an isolated CAS lesion as compared to multiple lesions within the cephalic arch, and the presence of diabetes were negatively associated with recurrent CAS. 19,21 It is well recognized that both anatomical and hemodynamic factors contribute to the development of CAS. Along the course of the cephalic vein's passage in the deltopectoral groove, it narrows as it approaches its junction with the central veins, giving rise to the characteristic arch structure in which high blood flow generated by fistula formation engenders turbulence and shear stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…19,20 On the other hand, an isolated CAS lesion as compared to multiple lesions within the cephalic arch, and the presence of diabetes were negatively associated with recurrent CAS. 19,21 It is well recognized that both anatomical and hemodynamic factors contribute to the development of CAS. Along the course of the cephalic vein's passage in the deltopectoral groove, it narrows as it approaches its junction with the central veins, giving rise to the characteristic arch structure in which high blood flow generated by fistula formation engenders turbulence and shear stress.…”
Section: Discussionmentioning
confidence: 97%
“…Studies revealed that CAS occurred more often in BCFs than in RCFs due to high blood flow flowing cephalic arch in BCFs, and severity of stenosis (%) at index visit and residual stenosis (%) after PTA were deemed predictive of its recurrence. 19,20 On the other hand, an isolated CAS lesion as compared to multiple lesions within the cephalic arch, and the presence of diabetes were negatively associated with recurrent CAS. 19,21…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They proposed that these geometrical changes were caused by hemodynamic differences in diabetics such as higher arterial pressures and blood flow velocities combined with narrower diameter vessels with calcifications 42 . A different study by Neves et al identified that diabetes was a risk factor for recurrent CAS after percutaneous intervention, but the authors were not able to pinpoint the exact reason for this finding 43 …”
Section: Cephalic Arch Stenosis (Cas)mentioning
confidence: 99%
“…42 A different study by Neves et al identified that diabetes was a risk factor for recurrent CAS after percutaneous intervention, but the authors were not able to pinpoint the exact reason for this finding. 43…”
Section: Etiologymentioning
confidence: 99%